Sustainable tourism practices in indigenous communities: The case of the Peruvian Andes - Barbieri, Carla E. (2019)
The Peruvian government has supported community-based tourism (CBT) for the last ten years seeking to improve the well-being of marginalized rural communities sustainably. Yet, the notion of sustainability among these CBT providers has not been formally assessed, nor the impact of different managerial models in such a notion. Thus, we interviewed members of seven CBT initiatives operating in the Peruvian Andes to evaluate their level of understanding of sustainability and their awareness of the impacts their activities produce. Analysis yielded five themes and 17 sub-themes which altogether illustrate interviewees’ understanding of sustainability attained throughout their path of developing CBT. Findings revealed these CBT initiatives implement many sustainable practices, likely due to the training they receive from supporting agencies. Notably, they assert CBT should remain complementary to agricultural livelihoods as to allow benefits to outweigh negative impacts. Findings also show management and networking inefficiencies in need of improvement to increase sustainability.